RISK FACTORS OF TEENAGE PREGNANCY IN SARAWAK: GROUNDED THEORY APPROACH - Agong, Christina Busak Henry Sum; Saimon, Rosalia (Malaysian Journal of Public Health Medicine, 2026)
Teenage pregnancy remains a significant public health concern in Sarawak, with rates among the highest in Malaysia, affecting the health and well-being of adolescent mothers, their children, and society. Despite its prevalence, locally grounded qualitative evidence on the risk factors specific to Sarawak’s multicultural and geographic context remains limited. This study addresses this gap by identifying the risk factors associated with teenage pregnancy in Sarawak, as the foundational phase in developing a culturally contextualised risk assessment tool for teenage pregnancy (TeenRAT). A qualitative grounded theory approach was utilized to explore the experiences of 20 mothers aged between 20 and 35, recruited from rural and urban settings across four divisions in Sarawak: Kuching, Sibu, Miri, and Limbang. They were recruited using a purposive sampling technique. In-depth interviews were conducted from February to October 2022 until data saturation was achieved. Data triangulation was obtained through focus group discussions with relevant stakeholders. Data analysis was guided by Strauss and Corbin’s grounded theory coding procedures using NVIVO-12 software. Ten themes and 38 sub-themes emerged as risk factors, with family dynamics and relationships identified as the key factor across themes. The findings provide a locally grounded evidence base for developing TeenRAT, which has the potential to support nurses, school health workers, and community health practitioners in early identification of adolescents at risk of teenage pregnancy in Sarawak.